2016
DOI: 10.1007/s13197-015-2135-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of water and alkali extractable arabinoxylan from wheat and rye under standardized conditions

Abstract: Arabinoxylans (AXs) are an important component of wheat and rye dough. They bind water, contribute to the formation of viscous dough and improve the quality of bread. For the application of AX fractions in bread making process, it is useful to record a quality profile of wheat fractions compared to the quality profile of rye fractions under standardized conditions. In this work water and alkali extractable AX containing fractions, from wheat- and rye wholemeal, were extracted under standardized conditions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 19 publications
3
24
1
Order By: Relevance
“…In such a dough yeast fermentation was hampered (Brandt & Ganzle, 2015), ethanol content was low (Table 1), and the content of sugars was higher than in other samples. In the present study, the effect of both arabinose and xylose was comparable, which seems to be in contradiction with the literature (Gobbetti et al, 2000), but it could be explained by known difficulties during degradation of AX molecules to monosaccharides by endo‐xylanases (Buksa, Praznik, Loeppert, & Nowotna, 2016).…”
Section: Resultscontrasting
confidence: 99%
“…In such a dough yeast fermentation was hampered (Brandt & Ganzle, 2015), ethanol content was low (Table 1), and the content of sugars was higher than in other samples. In the present study, the effect of both arabinose and xylose was comparable, which seems to be in contradiction with the literature (Gobbetti et al, 2000), but it could be explained by known difficulties during degradation of AX molecules to monosaccharides by endo‐xylanases (Buksa, Praznik, Loeppert, & Nowotna, 2016).…”
Section: Resultscontrasting
confidence: 99%
“…A similar relationship between WSP and WA was found by other authors [27]. A study conducted by Buksa et al [31,32] revealed that the ability of water soluble pentosans to bind water was significantly influenced, not only by their content, but also by their molecular mass. An increase in the mass of WSP cause an increase in flour water absorption.…”
Section: Resultssupporting
confidence: 82%
“…As a result, the hydrothermally extracted arabinoxylans were found to have a lower MW compared to the alkaline/hydrogen peroxide extract. Similar results were reported previously by Buksa et al [34]. Since the MW of the extracts obtained at 160 • C and with alkaline/hydrogen peroxide were below 100,000 g/mol, they should be considered as low MW-AX [15].…”
Section: Molecular Mass (Mw) Of Extracted Arabinoxylanssupporting
confidence: 90%